Work empowerment among cancer care professionals: A cross-sectional study - Siekkinen Mervi; Kuokkanen Liisa; Kuusisto Hannele; Leino-Kilpi Helena; Rautava Päivi; Rekunen Maijastiina; Seppänen Laura; Stolt Minna; Walta Leena; Sulosaari Virpi (United Kingdom, 2022)
Background: There is a growing understanding that empowerment of interprofessional personnel is linked to job satisfaction levels and quality of care, but little is known about empowerment in the context of cancer care. This study describes how interprofessional cancer care personnel perceive their performance and factors that promote work empowerment.
Methods: This cross-sectional study enrolled 475 (45.2%) of the 1050 employees who work at a regional cancer centre. The participants used two self-administered questionnaires - the Performance of an Empowered Personnel (PEN) questionnaire and Work Empowerment Promoting Factors (WEP) questionnaire - to report perceptions of work empowerment. Both questionnaires' categories comprise moral principles, personal integrity, expertise, future orientation, and sociality. The data were analyzed using IBM SPSS Statistics, Versions 24 and 25.
Results: Overall, the performance of work empowerment was evaluated as being rather high (overall sum score mean: 4.05; range: 3.51-4.41; scale: 1-5). The category that rated highest was moral principles (4.41), and the one rated lowest was the social category (3.51). The factors that promoted work empowerment also ranked high (3.93; range: 3.55-4.08; scale: 1-5), with personal integrity (4.08) the highest and future orientation (3.55) the lowest. Performance and factors that promoted work empowerment correlated positively, moderately, and highly statistically significantly (r = 0.531; p < 0.001). Statistically significant associations also were found between empowered performance of personnel and empowerment promoting factors (sex, education, leadership position, belonging to an interprofessional team, and time elapsed since training in interprofessional cooperation).
Conclusion: The personnel rated their performance and the factors perceived to promote work empowerment rather highly. Personal empowerment can be promoted through teamwork training and supportive management in interprofessional cancer care.